1996
DOI: 10.1097/00000658-199608000-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Study Comparing Laparoscopic Versus Open Repair of Perforated Peptic Ulcer Using Suture or Sutureless Technique

Abstract: ObjectiveThis study compares laparoscopic versus open repair and suture versus sutureless repair of perforated duodenal and juxtapyloric ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
263
3
13

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(291 citation statements)
references
References 13 publications
12
263
3
13
Order By: Relevance
“…Peptic ulcer perforation is a serious complication which affects almost 10 % of PUD patients. Overall, PUD accounts for more than 70 % of mortality associated with the disease [3,4] . Several potential predicting factors for perforation have been evaluated in the literature, including use of ulcerogenic drugs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Peptic ulcer perforation is a serious complication which affects almost 10 % of PUD patients. Overall, PUD accounts for more than 70 % of mortality associated with the disease [3,4] . Several potential predicting factors for perforation have been evaluated in the literature, including use of ulcerogenic drugs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…After surgery patients in laparoscopic group required significantly less parenteral analgesics than those who underwent open repair (1.2 days in group 1 vs 3.8 in Group 2, p>0.05) which is statistically significant. The Meta analysis published by Lau showed that eight out of 10 studies showed significant reduction in dosage of analgesics required in laparoscopic group [3,5]. Mean duration of resumption of normal diet was 2.4 with laparoscopic repair and 3.6 with laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in operative time is considered to be a risk factor for increased post-operative complications [24]. There is a constant effort to simplify the suturing technique, and this has evolved from the traditional omental plug or omentoplasty to simple suturing [27], clips [31] or suture less technique with sealants [32]. It remains to be seen whether this effort to reduce operating time is associated with increased risk of complications, i.e.…”
Section: Perforated Peptic Ulcermentioning
confidence: 99%
“…Wadaani in his prospective case series of 45 patients (2013) has used the irrigation selectively in cases with visible food remnants in peritoneal cavity, and this has been postulated as an independent factor in reducing the operative time [33]. Due to improving surgical skills, technology and better teamwork, a progressive reduction in operative times [94 min (Lau et al 1996), 75 min (Bertleff et al 2009) and 42 min (Wadaani 2013)] has been achieved in the past years [8].…”
Section: Perforated Peptic Ulcermentioning
confidence: 99%